Ausencia de roles paternos y su influencia en los trastornos de conducta de un adolescente de 14 años perteneciente a la Parroquia Balzapamba, cantón San Miguel Provincia Bolivar - Naranjo Morales, Carlos Xavier (2021)
The present study is focused and directed to make known what is the influence of the father and mother, their role, the absence or lack of the establishment of parental roles in the behavior disorders of a child, for the present study tools of use were used. clinical history, direct observation and semi-structured interview, psychometric tests, and the DSM-V diagnostic manual for the diagnosis of oppositional defiant disorder, in a 14-year-old adolescent, this study was carried out In the Balsapamba parish belonging to the canton of San Miguel de Bolívar, in the Bolívar province, the psychological intervention was carried out through the use of Cognitive Behavioral techniques to reduce dissocial behaviors and achieve that the adolescent achieves a better quality